Hitting Rock Bottom: Economic Hardship and Cheating - Livia Alfonsi; Michal Bauer; Julie Chytilová; Edward Miguel (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
This paper investigates whether economic hardship undermines preferences for honesty. We use controlled, high-stake measures of cheating for private benefit in a large sample of 5,664 Kenyans, exploiting three complementary sources of variation: experimentally manipulated monetary incentives to cheat, a randomized increase in the salience of one's own financial situation, and the Covid‑19 income shock (exploiting randomized survey timing, with respondents interviewed before vs. during the crisis). We find that cheating behavior is highly responsive to financial incentives in the experiment. Covid-19 economic hardship — marked by a 51% drop in monthly earnings — leads to a sharp increase in the prevalence of cheating, and the effect increases gradually with prolonged hardship. The effects are largest among the most economically impacted and are amplified when the salience of one's own financial situation is experimentally increased. The results demonstrate that while most individuals exhibit a strong preference against cheating under normal conditions (in line with the existing body of work), economic forces can account for a substantial share of variation in dishonesty: the estimated cheating rate rises from 29% under low stakes in normal times to 86% under high stakes during the crisis.
Keywords: D91; C93; O12; 330; economic hardship; honesty; cheating behavior; field experiment; Kenya